2013
DOI: 10.1098/rspb.2013.1708
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Classopollis pollen reveals evidence for unreduced (2 n ) pollen in the conifer family Cheirolepidiaceae during the Triassic–Jurassic transition

Abstract: Polyploidy (or whole-genome doubling) is a key mechanism for plant speciation leading to new evolutionary lineages. Several lines of evidence show that most species among flowering plants had polyploidy ancestry, but it is virtually unknown for conifers. Here, we study variability in pollen tetrad morphology and the size of the conifer pollen type Classopollis extracted from sediments of the Triassic-Jurassic transition, 200 Ma. Classopollis producing Cheirolepidiaceae were one of the most dominant and diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Similar observations exist in interspecific Brassica hybrids subject to cold stress (Mason et al 2011), while most hybrids already exhibit increased levels of unreduced gamete formation (Ramsey and Schemske 1998). Recent evidence supports that environmental stress and/or fluctuations could also have increased unreduced gamete levels at previous large-scale extinctions, as demonstrated by the increased number of unreduced fossil pollen found in the now extinct conifer family Cheirolepidiaceae at the Triassic-Jurassic transition 201.3 mya (Kurschner et al 2013). Abnormal gymnosperm pollen (Foster and Afonin 2005) and lycophyte spores (Visscher et al 2004) have also been reported at the Permian-Triassic transition 252.3 mya (Shen et al 2011).…”
Section: Enhanced Polyploid Establishment Through Mitigation Of the Msupporting
confidence: 58%
“…Similar observations exist in interspecific Brassica hybrids subject to cold stress (Mason et al 2011), while most hybrids already exhibit increased levels of unreduced gamete formation (Ramsey and Schemske 1998). Recent evidence supports that environmental stress and/or fluctuations could also have increased unreduced gamete levels at previous large-scale extinctions, as demonstrated by the increased number of unreduced fossil pollen found in the now extinct conifer family Cheirolepidiaceae at the Triassic-Jurassic transition 201.3 mya (Kurschner et al 2013). Abnormal gymnosperm pollen (Foster and Afonin 2005) and lycophyte spores (Visscher et al 2004) have also been reported at the Permian-Triassic transition 252.3 mya (Shen et al 2011).…”
Section: Enhanced Polyploid Establishment Through Mitigation Of the Msupporting
confidence: 58%
“…altitudinal gradients), as well as large‐scale climate changes (as shown in Kürschner et al . ; Vanneste et al . ) could substantially alter the dynamics of polyploid evolution, or at least fuel opportunities for establishment through the recurrent formation of new entities.…”
Section: Introductionmentioning
confidence: 99%
“…In other regions of the supercontinent Pangea and in East Greenland, the ETE is marked by a geologically transient ecological dominance of ferns and fern allies (87) belonging to extant fern families, many of which today have exclusively tropical and subtropical biogeographical distributions. Thermophilic conifers belonging to the extinct Cheirolepidiaceae family became dominant in the continental interiors in many global localities (22), perhaps aided by widespread fire disturbance (15) and their likely capacity for whole-genome duplication (81), which is generally rare in gymnosperms. Therefore, the pattern of global vegetation responses under super-elevated CO 2 is characterized by a loss of evenness (101) and local-to-regional-scale turnover (22, 87, 90, 98), but remarkably little global extinction at higher taxonomic ranks (30,166).…”
Section: Case Study Of Past Global Change: Astartekløft East Greenlandmentioning
confidence: 99%